DAMPAK PEMBUANGAN LIMBAH INDUSTRI BATU ALAM TERHADAP KUALITAS AIR IRIGASI DI KECAMATAN PALIMANAN KABUPATEN CIREBON - Uktiani, Arum (Universitas Negeri Semarang, 2016)
There are 38 natural stone industries in Palimanan District, Cirebon Regency which have no installation of wastewater processing so that the wastewater is directly discharged into irrigation canals Left Jamblang. The problem wasthat there was waste disposal impact of the natural stone industries to the irrigation water quality in PalimananDistrict. The purpose of this study is to determine the waste disposal impact of the natural stone industries to theirrigation water quality in Palimanan District. The location studied was fields irrigated by Left Jamblang of six villagesin Palimanan District with a population of Palimanan Left Jamblang irrigation water that went into the fields inPalimanan District. The sample used was the sampling area which had 8 samples with physics quality variable andirrigation of water chemistry. The methods of data collection were map interpretation and laboratory tests. The dataanalysis techniques used were the comparative analysis and overlay. The natural stone waste had an impact onirrigation water since the parameter values in irrigation water had increased rather than the parameter value on thesource of irrigation water. Though the waste of natural stone had effect on the irrigation water, there were only two ofthe seven parameters which indicated poor quality, namely pH and RSC. In the study area, irrigation water could stillbe used to irrigate the fields because it had three types of quality, which are very good, good, and good enough, butthere were pH and RSC parameters exceeding the quality standards which had pH 9 and RSC 2,639meq/l located in theKepuh Village. If it is ignored, then in certain period, it is likely to degrade quality of irrigation water.